2011
DOI: 10.1136/bcr.02.2011.3913
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal varices successfully treated with cyanoacrylate injection therapy

Abstract: Duodenal varices are a rare complication of portal hypertension secondary to liver cirrhosis. Compared to oesophageal varices, they bleed less often but are also more difficult to diagnose and treat. There is no established treatment for bleeding duodenal varices and different treatment strategies have been employed with variable results. The authors present a case of 52-year-old male who was admitted with melaena. Upper gastrointestinal endoscopy was performed which identified bleeding varices in the second p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…We saw obturation of varices in 3 of 5 cases; the rest were unavailable. In concordance with other reported cases, [9,11,16] cyanoacrylate injection seems to be effective and safe without serious adverse events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We saw obturation of varices in 3 of 5 cases; the rest were unavailable. In concordance with other reported cases, [9,11,16] cyanoacrylate injection seems to be effective and safe without serious adverse events.…”
Section: Discussionsupporting
confidence: 91%
“…Akazawa et al [8] showed successful management of duodenal variceal bleeding by EVL and subsequent BRTO. Malik et al [9] and Mora-Soler et al [10] reported 1 and 5 patients with duodenal variceal bleeding treated successfully with cyanoacrylate injection, respectively. Schmeltzer et al [11] presented a case of duodenal variceal bleeding successfully treated with EVL.…”
Section: Discussionmentioning
confidence: 99%
“…Currently it is advocated to start vasoactive medication and to try endoscopic measures if technically feasible, with band ligation for small varices only (due to the risk of a large mucosal defect) and cyanoacrylate injection being the most consensual 4 11–13. There are reports on alternative endoscopic techniques like human thrombin injection5 6 that may be less likely to cause thromboembolic complications 14.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports and case series include medical treatment with vasoactive drugs, elastic band ligation, cyanoacrylate4 and human thrombin injection5 6 as endoscopic modalities, transjugular intrahepatic portosystemic shunt (TIPS) and balloon-occluded retrograde transvenous obliteration (BRTO) by means of interventional radiology and, finally, performing a surgical shunt 3…”
Section: Introductionmentioning
confidence: 99%
“…1 Although a rare cause of gastrointestinal (GI) bleeding, they are reported to have a high mortality, around 40%. [1][2][3][4][5][6][7] Up to 17% of ectopic varices occur in the duodenum, 3 4 but they are not a common cause of variceal bleeding.…”
Section: Introductionmentioning
confidence: 99%